Internet Access on the Cheap: The Power of the Co-Op - Gudea , Sorin (Journal of Law and Governance, 2007)
Internet access in the former socialist block continues to lag behind more developed countries. Unequal access to Information Technology has produced uneven levels of participation in the networked economy and society. Internet access, which is important to maintaining a technologically competent labour force, is a staple in the developed countries. However, it continues to be limited in Romania. Would-be users are devising inventive solutions to the relatively costly access solutions in order to get on the Information Highway. A country case study of Internet access in Romania reveals the advent of self-established, co-operative networks providing shared Internet access - seemingly a unique and innovative approach. Several of the Internet access plans on the market are presented in this paper together with a discussion of cyber cafés and the home-grown, co-operative networks that seem to be popping up all over the country. Understanding the context within which these home-grown networks arise and prosper offers valuable lessons and ideas for transferring these approaches to other developing countries that, like Romania, are struggling to bridge the infamous digital divide.